Fear of Small Numbers An Essay on the Geography of Anger - Appadurai, Arjun (A John Hope Franklin Center Book, 2006)
The period since 1989 has been marked by the global endorsement of open markets, the free flow of finance capital and liberal ideas of constitutional rule, and the active expansion of human rights. Why, then, in this era of intense globalization, has there been a proliferation of violence, of ethnic cleansing on the one hand and extreme forms of political violence against civilian populations on the other?Fear of Small Numbers is Arjun Appadurai's answer to that question. A leading theorist of globalization, Appadurai turns his attention to the complex dynamics fueling large-scale, culturally motivated violence, from the genocides that racked Eastern Europe, Rwanda, and India in the early 1990s to the contemporary "war on terror." Providing a conceptually innovative framework for understanding sources of global violence, he describes how the nation-state has grown ambivalent about minorities at the same time that minorities, because of global communication technologies and migration flows, increasingly see themselves as parts of powerful global majorities. By exacerbating the inequalities produced by globalization, the volatile, slippery relationship between majorities and minorities foments the desire to eradicate cultural difference.Appadurai analyzes the darker side of globalization: suicide bombings; anti-Americanism; the surplus of rage manifest in televised beheadings; the clash of global ideologies; and the difficulties that flexible, cellular organizations such as Al-Qaeda present to centralized, "vertebrate" structures such as national governments. Powerful, provocative, and timely, Fear of Small Numbers is a thoughtful invitation to rethink what violence is in an age of globalization